DOES FINANCIAL DISCLOSURE INFLUENCE ISLAMIC DONATION-BASED CROWDFUNDING? THE MEDIATING ROLES OF TRUST AND REPUTATION - Amini, Azizah Khairina; Aligarh, Frank; Setiawan, Ade; Usnan, Usnan; Andraeny, Dita; Rachmawati, Dhina Pratiwi (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2024)
This study explores the impact of financial disclosure on the public's intention to donate through Islamic donation-based crowdfunding, with trust and reputation as mediating variables. This quantitative study used convenience sampling to collect data from 253 respondents using a Google Forms questionnaire. The data were analyzed using SEM-PLS. The results indicate that financial disclosure has a positive and significant relationship with trust, reputation, and donation intention. Trust and reputation positively and significantly influence the intention to donate through crowdfunding platforms. Additionally, trust and reputation partially mediate the relationship between financial disclosure and donation intention on crowdfunding platforms. In conclusion, effective financial disclosure by a crowdfunding platform directly enhances public trust and the platform’s reputation. This study is expected to increase public awareness and assist crowdfunding platforms in developing policies and strategies to meet public expectations.